2019
DOI: 10.1186/s12864-019-6076-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the effect of C-C chemokine receptor 5 deficiency on cell response to Toxoplasma gondii in brain cells

Abstract: Background Infection with Toxoplasma gondii is thought to damage the brain and be a risk factor for neurological and psychotic disorders. The immune response-participating chemokine system has recently been considered vital for brain cell signaling and neural functioning. Here, we investigated the effect of the deficiency of C-C chemokine receptor 5 (CCR5), which is previously reported to be associated with T. gondii infection, on gene expression in the brain during T. gondii infection and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Total RNA was extracted with TRI Reagent ® (Sigma-Aldrich), according to the manufacturer's protocol. The extracted RNA was individually subjected to RNA-seq, according to the protocol used in our previous study [20,35,37]. Briefly, 1 µg of total RNA was subjected to poly-A selection.…”
Section: Rna-seq Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA was extracted with TRI Reagent ® (Sigma-Aldrich), according to the manufacturer's protocol. The extracted RNA was individually subjected to RNA-seq, according to the protocol used in our previous study [20,35,37]. Briefly, 1 µg of total RNA was subjected to poly-A selection.…”
Section: Rna-seq Analysismentioning
confidence: 99%
“…All treatments and subsequent analyses were performed on individual transcripts. The data of WT samples has been used in our previously published articles [35,37] because all the samples in these articles and the present study were prepared simultaneously. Raw sequence reads were subjected to quality control, and the cleaned reads were mapped to the reference mouse genome (mm10) with CLC Genomics Workbench version 10 (CLC bio, Aarhus, Denmark) (read mapping parameters: minimum fraction length of read overlap = 0.95, minimum sequence similarity = 0.95).…”
Section: Rna-seq Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, CCR5 absence can increase susceptibility to T. gondii (Bonfá et al, 2014; Khan et al, 2006). Finally, a recent study suggested that CCR5 participates in the regulation of inflammatory response, tissue injury and elimination of T. gondii infection in the brain (Kobayashi et al, 2019).…”
Section: Ccr5 and Ccr5δ32 In Parasitic Infectionsmentioning
confidence: 99%
“…Raw counts were normalized using the Benjamini and Hochberg's approach for controlling the false discovery rate (FDR) [38]. A corrected P-value of 0.005 and log 2 (Fold change) of 1.2 were set as the threshold for significantly differential expression [39,40].…”
Section: Differential Expression Analysismentioning
confidence: 99%